Fast and Efficient IP Handover in IEEE 802.11 Wireless LANs - Christos Bouras; Ioanna Sampraku; T Karoubalis (The 2004 International Conference on Wireless Networks (ICWN 04), Las Vegas, Nevada, USA, 2004)
This paper presents an effective and simple solution to the problem of Layer 3 (L3) handover in IEEE 802.11 wireless LANs (WLANs), so as to extend the IP mobility area of 802.11 wireless Stations (STAs). The IEEE 802.11f Inter-Access Point Protocol (IAPP), handles the Layer 2 (L2) mobility of STAs during L2 (intra-network) handovers, and offers IP connectivity via L2 specific methods. Instead of using a different protocol for the L3 mobility management of STAs, such as Mobile IP (MIP) [4] or a MIP-variant, the IAPP protocol is extended so as to also support the inter-network (L3) movements of 802.11 STAs. The proposed IAPP-based mechanism supports host mobility and offers substantial uninterrupted wireless IP-connectivity, even after L3 movements. The cornerstones of this mechanism are the zero-delay IP movement detection and the zero over-the-air IP signaling during IP handover establishment, which lead to seamless (very fast) and smooth IP handoffs. This fast IP-handoff method is especially suitable to 802.11 systems, as it has better performance than traditional MIP-based methods (shorter handover delays, near zero packet loss), while makes IP roaming transparent to the mobile STAs.